Impacto da radiofrequência transvaginal na força da musculatura pélvica de mulheres com incontinência urinária - Jorge, Luisa Braga (2021)
Introduction: Urinary incontinence (UI) is defined as any involuntary loss of urine. It has a high prevalence, affecting mainly elderly women and having a great negative impact on quality of life. Currently, conservative treatment is the first therapeutic option, focusing on pelvic muscle training exercises (TMAP). Due to the growing advancement of technology, new therapeutic resources have emerged, such as radio frequency (RF). There is little knowledge about the functioning of the pelvic floor muscles after RF and its impact on UI. Objective: To verify the effects of transvaginal RF on pelvic muscle strength (PF) in women with UI. Methods: Randomized clinical trial, composed of postmenopausal women, diagnosed with exertional or mixed UI with predominance of exertion. The participants were divided into a control group (CG), which received treatment through TMAP + transvaginal RF with the device turned off, and the intervention group (IG), which received the same treatment, but with the device at 45 degrees celsius. 1 session was held per month, totaling 3 sessions. Results: Participants were characterized as 32 women, with a mean age of 58.6±5 years. Sociodemographic, clinical, obstetric, irritant foods and associated diseases did not show significant differences between groups. Regardless of the form of treatment, PFM strength increased between pre-intervention (2.8±0.99) and post-intervention (3.5±1.4) p<0.0001. In the IG, 15 women participated, of which only 1 decreased strength, going from grade 4 to grade 3. In the CG, of 17 participants, all showed an increase or maintained strength. The GI group had a higher frequency (33%) of individuals who managed to reach the maximum degree, while in the CG, 17% reached the maximum degree. Participants rated the improvement of symptoms as 76.0±23.7 in the IG and 75.0±10.7 in the CG. For the overall improvement with the treatment, we identified 82.3±15.9 in the IG and 85.6±15.0 CG. Conclusion: The treatment, in general, showed a significant increase in PFM strength in both IG and CG. The gain obtained in strength did not differ between those who received only conventional treatment and those who received RF concomitantly. The report of treatment satisfaction and symptom improvement was not altered by the use of RF. Therefore, RF seemed to be a promising treatment, although not having the expected effects. However, a long-term segment is recommended, as well as the development of new randomized clinical studies with more robust samples and other assessment factors, including biochemical and histochemical markers to assess the efficiency of radiofrequency in the treatment of urinary incontinence in postpartum